Strangulated internal hernia underneath right external iliac artery: A case report - Abdelilah Elbakouri; A Lamnaouer; M Bouali; K Elhattabi; F Bensardi; A Fadil (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
Small bowel obstruction following internal herniation under the external iliac artery after total hysterectomy with pelvic lymph node dissection is a rare entity. We describe a case of strangulated internal hernia between the right external iliac artery and the psoas muscle as a late complication after 3 years of radical hysterectomy with pelvic lymphadenectomy. Retroperitoneal closure may be an appropriate procedure to effectively prevent such internal hernias. the emergency CT scan was used to diagnose a flange occlusion in the context of the situation. it was only during surgical exploration that the cause of the occlusion was revealed as an internal hernia. a resection of the ischemic bowel was performed with retroperitonealization of the artery.